PERLINDUNGAN HUKUM TERKAIT PEMEGANG HAK MILIK ATAS TANAH DALAM KEPEMILIKAN SERTIFIKAT GANDA(Studi Kasus Putusan Mahkamah Agung Nomor 3061 K/Pdt/2022) - Muhammad Ridwan Rasyid, (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
Legal certainty is one of the conditions that must be met in law enforcement, which means that someone will be able to get something that is expected in certain circumstances. In this case the Basic Agrarian Law lays the foundation which will later create legal certainty and protection for Indonesian citizens. According to Article 19 UUPA Number 5 of 1960 which states "To ensure legal certainty by the Government, land registration is carried out throughout the territory of the Republic of Indonesia according to the provisions regulated by Government Regulations. The problem occurred in the Supreme Court Decision Number 3061 K/Pdt/2022. In this case, there are problems related to overlapping land title certificates. This results in unclear norms resulting in legal uncertainty. The problem that will be discussed is how the judge's considerations are related to the Supreme Court decision Number 3061 K/Pdt/2022. The research method used is normative juridical with statutory and case approaches. The conclusion in this paper is that the judge's consideration regarding the Supreme Court Decision Number 3061 K/Pdt/2022 fulfills 3 (three) elements, namely legal certainty, justice and expediency. However, in considering the decision, the judge leaned on legal certainty. Keywords: Legal Protection, Multiple Property Rights Certificates, Legal Certainty, Judge Considerations, Supreme Court Decisions